Conditioned media from human palatine tonsil mesenchymal stem cells regulates the interaction between myotubes and fibroblasts by IL‐1Ra activity. Issue 1 (13th September 2016) - Cho, Kyung‐Ah; Park, Minhwa; Kim, Yu‐Hee; Woo, So‐Youn; Ryu, Kyung‐Ha
Abstract: Saturated free fatty acids (FFAs) act as lipid mediators and induce insulin resistance in skeletal muscle. Specifically, in obesity‐related diseases such as type 2 diabetes, FFAs directly reduce insulin sensitivity and glucose uptake in skeletal muscle. However, the knowledge of how FFAs mediate inflammation and subsequent tissue disorders, including fibrosis in skeletal muscle, is limited. FFAs are a natural ligand for toll‐like receptor 2 (TLR2) and TLR4, and induce chronic low‐grade inflammation that directly stimulates skeletal muscle tissue. However, persistent inflammatory stimulation in tissues could induce pro‐fibrogenic processes that ultimately lead to perturbation of the tissue architecture and dysfunction. Therefore, blocking the link between inflammatory primed skeletal muscle tissue and connective tissue might be an efficient therapeutic option for treating obesity‐induced muscle inactivity. In this study, we investigated the impact of conditioned medium obtained from human palatine tonsil‐derived mesenchymal stem cells (T‐MSCs) on the interaction between skeletal muscle cells stimulated with palmitic acid (PA) and fibroblasts. We found that PA‐treated skeletal muscle cells actively secreted interleukin‐1β (IL‐1β) and augmented the migration, proliferation and expression of fibronectin in L929 fibroblasts. Furthermore, T‐CM inhibited the skeletal muscle cell‐derived pro‐fibrogenic effect via the production of the interleukin‐1 receptor antagonist (IL‐1Ra), which is an inhibitor of IL‐1 signalling. Taken together, our data provide novel insights into the therapeutic potential of T‐MSC‐mediated therapy for the treatment of pathophysiological processes that occur in skeletal muscle tissues under chronic inflammatory conditions.